2021
DOI: 10.1029/2021ja029618
|View full text |Cite
|
Sign up to set email alerts
|

Drop of Solar Wind at the End of the 20th Century

Abstract: Variations in the solar wind (SW) parameters with scales of several years are an important characteristic of solar activity and the basis for a long‐term space weather forecast. We examine the behavior of interplanetary parameters over 21–24 solar cycles (SCs) on the basis of the OMNI database (https://spdf.gsfc.nasa.gov/pub/data/omni). Since changes in the parameters can be associated with both changes in the number of different large‐scale types of SW and with variations in the values of these parameters at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
28
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 74 publications
10
28
3
Order By: Relevance
“…As a result of this analysis, the following important conclusion can be drawn. In addition to the well-known fact that in 23-24 solar cycles the number of disturbed types of solar wind (ICME and related Sheath types) sharply decreased, at the end of the 20th century and the beginning of the 21st century there is a noticeable drop (by 20-40%) in the values of the parameters plasma and magnetic field in various types of solar wind and the low level of parameters persists or continues to decrease in 23-24 cycles [Yermolaev et al, 2021].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this analysis, the following important conclusion can be drawn. In addition to the well-known fact that in 23-24 solar cycles the number of disturbed types of solar wind (ICME and related Sheath types) sharply decreased, at the end of the 20th century and the beginning of the 21st century there is a noticeable drop (by 20-40%) in the values of the parameters plasma and magnetic field in various types of solar wind and the low level of parameters persists or continues to decrease in 23-24 cycles [Yermolaev et al, 2021].…”
Section: Discussionmentioning
confidence: 99%
“…The geoeffectiveness of SC 24 MCs relative to the ones in SC 23 declined by 49%; the geoeffectiveness of sheaths ahead of MCs declined by 59% [23]. Yermolaev et al [30] showed the reduced geoeffectiveness to be similar in non-cloud ejecta and sheath. In addition, these authors compared the geoeffectiveness of various solar wind structures that occurred in SCs 21-24 and found drastic reduction of geoeffectiveness in SC 24 compared to that in other cycles.…”
Section: Impact Of Weak Solar Activity In Cycle 24 On Space Weathermentioning
confidence: 96%
“…The altered properties of CMEs resulted space weather that is milder than what is expected from the reduced activity alone. The same applies to space weather caused by CIRs [4,29,30]. Instead of looking at the intense geomagnetic storms, if one starts with the magnetic clouds (MCs) and examines their space weather impact, the reduction in geoeffectiveness (as measured by Dst) is again clear [23,30].…”
Section: Impact Of Weak Solar Activity In Cycle 24 On Space Weathermentioning
confidence: 99%
See 1 more Smart Citation
“…This longer term data set allows us to investigate the Gleissberg cycle variation of inner belt protons (Feynman & Ruzmaikin, 2011;Gleissberg, 1944;Pulkkinen et al, 2001;Svalgaard et al, 2005). Feynman and Ruzmaikin (2011) described the Centennial Gleissberg Cycle as an approximately century-long sinusoidal variation in the intensity of solar maximum well established in sunspot number, finding evidence to suggest that Solar Cycles 23 and 24 represent a minimum of this 80 to 100-year cycle (Yermolaev et al, 2021) which follows the higher activity level of the early space age going back to the 1960 solar maximum. Several studies predict a weak solar maximum for Solar Cycle 25 (c.g.…”
mentioning
confidence: 99%